Study of the Variations of Asterion, Pterion & Inion in Human Dry Skulls & its Anthropological importance
Background and objectives: Asterion is the meeting point of three bones namely parietal, temporal and occipital bones in the norma lateralis of all human skulls the variations showed a pattern of formations. Pterion is the point of convergence of the sutures between the frontal, sphenoid, parietal and squamous temporal bones. Asterion have profound surgical importance. Materials and methods: Good intact skulls from different medical college of Nepal were used for the present study. Each skull was studied in detail regarding the formation of Asterion, Pterion on both sides and associated findings were observed. Sixty eight dry unknown human skulls constituted the materials for the present study. The observation was made on Asterion, Pterion & Inion. This study was done in the departments of Anatomy in different medical colleges of Nepal between the years 2019-2021. Results: Incidence of asterion with wormian bones on the right side was 4.41% that of the left side 5.88%. More number of H shaped pterion on the right side [80.82%